The Prospects OfShark Catfish(Pangasius hypothalmus) Farming Development In Kelurahan Palas, Rumbai Subdistricts, Pekanbaru City, Riau Province - Judhi Eka Pernandes; Lamun Bathara; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in February 2016. The purpose research is analyzing non-financial and financial feasibility study of Shark catfish farming. The method used are survey and determine respondents are non-random sampling technique (proportional sampling) that concluding the respondent is 5 people. The analysis of non-financial feasibility study, explained the business of Shark catfish farming feasible to develop, from aspects markets, opportunities market of Shark catfish is very large to domestic and international markets, on the technical farming aspects and management aspect is quite normal proper of Shark catfish farming in general, but these efforts have been able to run well. Financial analysis of the business means, that businesses are feasibility to do and developed. The total production cost are Rp.87.373.840,- grossed Rp.126.000.000,- so the benefit are Rp.38.626.160,- the feasibility of their business calculations BCR valued are 1.44 that interpretation the business advantageously, FRR valued are 44.2%, that means a good thing to do and PPC valued are 20.3 that defines the payback period of investments is not long.Keywords: Prospects, Feasibility, Development, Shark Catfish, Non-Financial, Financial